The Effect of Strategic Leadership on the Organisational Effectiveness in the Presence of Moderating Influence of Knowledge Management: The Case Study of Public Sector - Soonthornpipit, Hathaipan (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: The key aim behind undertaking this study is to find the effect that strategic leadership induces on the organisational effectiveness with the moderating role played by knowledge management Design/Method/Approach: Quantitative design has been adopted to test and identify the moderating effect of knowledge management in the midst of the relationship between OE (organisational effectiveness) and SL (strategic leadership). A self-administered questionnaire has been used for data collection whereas sample of 386 employees working in the public sector of Malaysia has been selected. SEM technique has been utilised through SmartPLS in order to test the direct effect, indirect effects of independent and moderating variable. Findings: The study found that there KM significantly moderates the relationship between SL and OE thereby confirming the indirect effect of SL with OE. Additionally, the direct effect of KM on OE has also been computed meanwhile, the direct effect of SL on OE has also been confirmed. Practical Implication: The study has implications for the public sector of Malaysia that can comprehend the information and use the findings for further increasing efficiency in knowledge management and for organisational effectiveness in the region.